Clinical decision-making in the treatment of periodontitis with new classification system of periodontal diseases - Deepak Sharma; Shalu Chandna Bathla; Pravesh Kumar Jhingta; Ankit Mahajan (Wolters Kluwer Medknow Publications, 2021)
Clinical application of the new classification of periodontal diseases requires knowledge of case definitions, parameters, and criteria of different categories and subcategories to arrive at final diagnosis. Correct implementation of the new classification of periodontitis is possible by understanding of the basic rules and guidelines, clarification of complex issues, and use of evidence-based dental practices. Step-wise sequence should be adopted to diagnose a patient with periodontitis. The authors, based on the current scientific evidence and clinical experience, have described specific decision-making algorithms of the diagnostic process and treatment plans of various subcategories of periodontitis.